Nilai Pendidikan Karakter dalam Kanal Youtube Riri Cerita Anak Interaktif : Kajian Sastra Siber - Ayu Wandana Yuantika; Rianna Wati (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2023)
This article examines children's literature in cyberspace. The development of increasingly sophisticated technology requires humans to keep up with the times. The existence of literature as a forum for education has been done for a long time. At the present time the development of literature as a forum for children's education is starting to be carried out in the cyber realm. Various platforms for spreading the values of character education to children are quite extensive, one of which is through the YouTube application, especially on the YouTube channel Riri Interactive Children's Stories which has 1.04 million subscribers. On Riri's YouTube channel Interactive Children's Stories, eighteen character education values were found which include; (1) Religious, (2) Honest, (3) Tolerance, (4) Discipline, (5) Hard work, (6) Creative, (7) Independent, (8) Democracy, (9) Curiosity, (10 ) National spirit, (11) Love of the motherland, (12) Appreciate achievements, (13) Friendly/communicative, (14) Love peace, (15) Love to read, (16) Care for the environment, (17) Care for social and (18 ) Responsible.